2004
DOI: 10.1103/physrevb.70.155404
|View full text |Cite
|
Sign up to set email alerts
|

Linearity and additivity in cluster-induced sputtering: A molecular-dynamics study of van der Waals bonded systems

Abstract: Using molecular-dynamics simulation, we study sputtering of a condensed-gas solid induced by the impact of atomic clusters with sizes 1 ഛ n ഛ 10 4 . Above a nonlinear onset regime, we find a linear increase of the sputter yield Y with the total energy E of the bombarding cluster. The fitting coefficients in the linear regime depend only on the cluster size n such that for fixed bombardment energy, sputtering decreases with increasing cluster size n. We find that to a good approximation the sputter yield in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
99
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 29 publications
9
99
1
Order By: Relevance
“…2a, the total sputtering yield increases with the primary kinetic energy if the projectile size is kept constant. Such behaviour has already been reported in the previous studies with cluster projectiles [7,8]. It has been also observed that above certain threshold energy, the yield increases linearly with the kinetic energy [7,8].…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…2a, the total sputtering yield increases with the primary kinetic energy if the projectile size is kept constant. Such behaviour has already been reported in the previous studies with cluster projectiles [7,8]. It has been also observed that above certain threshold energy, the yield increases linearly with the kinetic energy [7,8].…”
Section: Resultssupporting
confidence: 66%
“…3, our data support this observation again only partially. Indeed, below ε ≈ 300 eV/nucleon Y n dependence on ε is similar to the trend reported in [7,8]. However, at larger ε there is a distinctive deviation from this trend and ultimately the yield per nucleon even decreases with the increase of ε.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…A number of simulation studies and experiments were performed on the impact of atomic clusters on atomic targets -for example, metals, but also organic targets -with the aim of exploring the dependence of the crater sizes and sputter yields on the projectile characteristics (Anders et al 2004;Samela & Nordlund 2008;Anders et al 2009;Anders & Urbassek 2013;Seah 2013;Seah et al 2014). In these studies it was found that -above a threshold regime -the main projectile characteristic affecting crater volume and ejection yield is the total projectile energy.…”
Section: Introductionmentioning
confidence: 99%